Enhancing saline stress tolerance in soybean seedlings through optimal NH4+/NO3− ratios: a coordinated regulation of ions, hormones, and antioxidant potential - Noor, Javaria; Ahmad, Izhar; Ullah, Abd; Iqbal, Babar; Anwar, Shazma; Jalal, Arshad [UNESP]; Okla, Mohammad K.; Alaraidh, Ibrahim A.; Abdelgawad, Hamada; Fahad, Shah (Springer Nature, 2024)
Background: Nitrogen (N) availability is crucial in regulating plants’ abiotic stress resistance, particularly at the seedling stage. Nevertheless, plant responses to N under salinity conditions may vary depending on the soil’s NH4+ to NO3− ratio. Methods: In this study, we investigated the effects of different NH4+:NO3− ratios (100/0, 0/100, 25/75, 50/50, and 75/25) on the growth and physio-biochemical responses of soybean seedlings grown under controlled and saline stress conditions (0-, 50-, and 100-mM L− 1 NaCl and Na2SO4, at a 1:1 molar ratio). Results: We observed that shoot length, root length, and leaf-stem-root dry weight decreased significantly with increased saline stress levels compared to control. Moreover, there was a significant accumulation of Na+, Cl−, hydrogen peroxide (H2O2), and malondialdehyde (MDA) but impaired ascorbate-glutathione pools (AsA-GSH). They also displayed lower photosynthetic pigments (chlorophyll-a and chlorophyll-b), K+ ion, K+/Na+ ratio, and weakened O2•−-H2O2-scavenging enzymes such as superoxide dismutase, catalase, peroxidase, monodehydroascorbate reductase, glutathione reductase under both saline stress levels, while reduced ascorbate peroxidase, and dehydroascorbate reductase under 100-mM stress, demonstrating their sensitivity to a saline environment. Moreover, the concentrations of proline, glycine betaine, total phenolic, flavonoids, and abscisic acid increased under both stresses compared to the control. They also exhibited lower indole acetic acid, gibberellic acid, cytokinins, and zeatine riboside, which may account for their reduced biomass. However, NH4+:NO3− ratios caused a differential response to alleviate saline stress toxicity. Soybean seedlings supplemented with optimal ratios of NH4+:NO3− (T3 = 25:75 and T = 4 50:50) displayed lower Na+ and Cl− and ABA but improved K+ and K+/Na+, pigments, growth hormones, and biomass compared to higher NH4+:NO3− ratios. They also exhibited higher O2•−-H2O2-scavenging enzymes and optimized H2O2, MDA, and AsA-GSH pools status in favor of the higher biomass of seedlings. Conclusions: In summary, the NH4+ and NO3− ratios followed the order of 50:50 > 25:75 > 0:100 > 75:25 > 100:0 for regulating the morpho-physio-biochemical responses in seedlings under SS conditions. Accordingly, we suggest that applying optimal ratios of NH4+ and NO3− (25/75 and 50:50) can improve the resistance of soybean seedlings grown in saline conditions.
Keywords: Abiotic stress; Nitrogen form; Nutrients management; Physiological responses; Salinity resistance